Participation marketing : unleashing employees to participate and become brand storytellers - Brito, Michael (London, United Kingdom ; New York, NY : Kogan Page Limited, 2018)
"This book will help business leaders think strategically about employee advocacy as a new channel to market and will show them how to develop trusted brand messages. Participation in company activity and sharing content not only helps reach wider communities with trusted peer-to-peer endorsements, it also reinforces the credibility of a company as a positive brand experience. Alongside higher employee engagement, retention and productivity, Participation Marketing shows you how to work with the most vital influencers that any organization can have: its employees"--
Introduction: Your people are your brand / by Russ Fradin -- Employee advocacy : making a believer out of you -- The future of work : the new office, inside and out -- Contextualizing the marketplace for employee activation -- The psychology of 'what's in it for me?' and how it affects employee advocacy -- For brands, employee advocacy is a business imperative -- Employee advocacy as a business model -- Employee advocacy : a model for disruption -- Building your employee activation plan : who is responsible for what? -- Identifying, segmenting and training the workforce for brand engagement -- Bringing employee storytelling to life -- Choosing the right employee advocacy technology
Includes bibliographical references and index
Keywords: Branding (Marketing); Marketing -- Management; Management -- Employee participation; Corporate culture; Employee motivation